Supercapacitive performance of N-doped graphene/Mn3O4/Fe3O4 as an electrode material - Chong, Beng Meng; Azman, Nur Hawa Nabilah; Mohd Abdah, Muhammad Amirul Aizat; Sulaiman, Yusran (MDPI, 2019)
Nitrogen-doped graphene (NDG) and mixed metal oxides have been attracting much attention as the combination of these materials resulted in enhanced electrochemical properties. In this study, a composite of nitrogen-doped graphene/manganese oxide/iron oxide (NDG/Mn3O4/Fe3O4) for a supercapacitor was prepared through the hydrothermal method, followed by freeze-drying. Field emission scanning electron microscopy (FESEM) images revealed that the NDG/Mn3O4/Fe3O4 composite displayed wrinkled-like sheets morphology with Mn3O4 and Fe3O4 particles attached on the surface of NDG. The presence of NDG, Mn3O4, and Fe3O4 was characterized by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The electrochemical studies revealed that the NDG/Mn3O4/Fe3O4 composite exhibited the highest specific capacitance (158.46 F/g) compared to NDG/Fe3O4 (130.41 F/g), NDG/Mn3O4 (147.55 F/g), and NDG (74.35 F/g) in 1 M Na2SO4 at a scan rate of 50 mV/s due to the synergistic effect between bimetallic oxides, which provide richer redox reaction and high conductivity. The galvanostatic charge discharge (GCD) result demonstrated that, at a current density of 0.5 A/g, the discharging time of NDG/Mn3O4/Fe3O4 is the longest compared to NDG/Mn3O4 and NDG/Fe3O4, indicating that it had the largest charge storage capacity. NDG/Mn3O4/Fe3O4 also exhibited the smallest resistance of charge transfer (Rct) value (1.35 Ω), showing its excellent charge transfer behavior at the interface region and good cyclic stability by manifesting a capacity retention of 100.4%, even after 5000 cycles.